Raising Autism Awareness among Greek Teachers. Issue 1 (2nd January 2019) - Giannopoulou, Ioanna; Pasalari, Evdokia; Korkoliakou, Panagiota; Douzenis, Athanasios
Abstract: A recent special education legislation reform in Greece puts emphasis on the inclusion of pupils with special educational needs into mainstream schools. The purpose of the present study was to investigate knowledge of ASD among 67 mainstream nursery and primary classroom teachers, and evaluate the effectiveness of a half-day ASD awareness seminar in increasing their knowledge of the disorder. A self-report ASD Knowledge Questionnaire (ASD-KQ), developed for the purpose of this study, was used before and after the ASD awareness seminar. The results indicated a significant shift from low to moderate/high level of ASD knowledge among teachers with no previous training in special education and/or autism (58.7%), whereas this shift did not reach significance level in the teacher's group with previous training (16.7%) after the seminar. The present findings have important implications for the development of training programmes of practising teachers.